Examination of the Impact of Descriptive Evaluation on the Academic Achievement of Students in the Evaz Region - Mashinchi, Ali Asghar (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Objective: This study examines the impact of descriptive evaluation on the academic achievement of students in the Evaz region. Methods and Materials: It is an applied research study in terms of its objective and a descriptive-survey type in terms of its execution. The statistical population of the study includes all teachers in the Evaz region during the academic year 2017-2018, totaling 604 individuals (258 women and 346 men). Using the Morgan table and stratified random sampling, a sample of 236 individuals (101 women and 135 men) was selected. Research data were collected using academic achievement and descriptive evaluation metrics. The content validity of the research questionnaires was confirmed by experts. Additionally, using factor analysis, the validity of the descriptive evaluation questionnaire was confirmed at 0.93 and the academic achievement questionnaire at 0.86. The reliability of the research questionnaires was also determined using Cronbach’s alpha method, with the descriptive evaluation questionnaire at 0.90 and the academic achievement questionnaire at 0.92. The obtained data were analyzed using descriptive and inferential statistics. Findings: The research results indicated that descriptive evaluation has a significant impact on students’ academic achievement. Conclusion: The principal should identify the existing knowledge in the school, making it accessible and extractable. To achieve this, the principal should create a platform for expanding human interactions and relationships within networks to uncover and extract implicit knowledge.